Effects of Metal–Support Interaction in the Electrocatalysis of the Hydrogen Evolution Reaction of the Metal-Decorated Titanium Dioxide Supported Carbon - Ometto, Felipe Berto; Paganin, Valdecir Antonio; Hammer, Peter [UNESP]; Ticianelli, Edson Antonio (MDPI, 2023)
It has been found that the electrocatalytic properties of metallic nanoparticles supported on transition metal oxides are affected by the existing strong metal–support interaction (SMSI). Herein, the effects of SMSI on the electrocatalysis of the hydrogen evolution reaction (HER) were investigated in acid electrolyte by using Pt and Ag nanoparticles supported on carbon and titanium oxide (TiO2). High-resolution transmission electron microscopy (HR–TEM) images showed that Pt and Ag nanoparticles present a spherical shape at the TiO2 support and an average size distribution of around 4.5 nm. The X-ray photoelectron spectroscopy (XPS) results for Pt/TiO2/C and Ag/TiO2/C evidenced higher amounts of surface oxides in the metallic particles, when compared to the materials supported on carbon. Consistently, electrode polarization and electrochemical impedance results revealed that both metal–TiO2 and metal–C-supported catalysts were more active in catalyzing the HER than the corresponding carbon-supported materials, with Pt presenting better results. These differences in the HER activities were related to the electronic effects of the TiO2/C substrate on the Pt and Ag metals, introduced by strong metal-support (SMSI) in the metal–TiO2/C catalysts.
Keywords: activity-property correlations; charge transfer; decoration effects; hydrogen evolution reaction; support effects